EFEKTIVITAS SKIN BARRIER ACRYLATE TERPOLIMER TERHADAP KEJADIAN MEDICAL ADHESIVE RELATED SKIN INJURY (MARSI) PADA ANAK YANG DIRAWAT DI RUANG INTENSIF RSUPN DR. CIPTO MANGUNKUSUMO - Mutifa, Juanda; Nurhaeni, Nani; Apriyanti , Efa (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: For a long time, the use of medical adhesives in invasive device installation procedures can cause medical adhesive related to skin injury (MARSI) in children; in order to minimize the risk of MARSI incidents, so that a skin barrier is needed before applying the adhesive. OBJECTIVE: The purpose of this study is to determine the effectiveness of acrylate terpolymer skin barrier against medical adhesive related to skin injury (MARSI) prevention  in children who are treated at the intensive care unit. METHOD: This study used a true experimental design which involved 46 children; it was divided into an intervention group of 24 respondents and a control group of 22 respondents who were treated by using medical adhesive due to the procedure for inserting an endotracheal tube and nasogastric tube. Samples were taken by using random sampling technique. The risk level of skin injury was assessed by using the Braden Q scale and the MARSI incidents were observed by using the observational format. RESULT: The results showed that the acrylate terpolymer skin barrier was effective in reducing the MARSI in children who were treated at the intensive care unit with having a p-value of 0.03 (α <0.05). The use of an acrylate terpolymer skin barrier can be recommended to minimize the incidence of MARSI in children. CONCLUSION: The use of acrylate terpolymer skin barrier significantly minimizes the incidence of MARSI in children.